Qawaid Fiqhiyyah Tentang Zihar - Heriamsyah Simanjuntak; Mhd Amar Adly; Heri Firmansyah (Jurnal Budi Pekerti Agama Islam, 2024)
This research aims to examine the concept of Zihar in the Islamic context, which refers to the action of a husband who utters words that resemble his wife with something that is haram for him, such as a mother or sister, without being accompanied by a legal divorce. The practice of Zihar is seen as a reprehensible act and contrary to the principles of justice and equality in husband-wife relationships in Islam. This research uses qualitative research methods which aim to describe data through a series of sentences. The method chosen is the descriptive method, which relies on data sources in the form of words, images and information from books, journals and other scientific works. The research results show that in the Qur'an, Allah confirms the prohibition against Zihar and determines kafarat (ransom) as a consequence of this action. Zihar speech should be avoided by husbands under all circumstances, emphasizing the importance of respect, justice and equality in the husband-wife relationship. Zihar is considered an illegal form of divorce in Islam, and although it does not directly result in divorce, makes the wife unlawful for the husband without a legal divorce process. The importance of good and understanding communication between husband and wife is also highlighted to prevent actions that are detrimental to either party. In addition, the consequences of Zihar in Islamic law and its impact in maintaining harmony and justice in husband-wife relationships are explained in detail. This research also confirms that Zihar is not an accepted practice in Islamic teachings, and that this act can have serious consequences in the husband-wife relationship. In a modern context, understanding the laws of Zihar can help Muslims maintain a just and harmonious marriage relationship in accordance with religious teachings.